Pharmacokinetics of Gd(DO3A-Lys) and MR imaging studies in an orthotopic U87MG glioma tumor model - Chandrasekharan, Prashant (2016)
Pharmacokinetics of Gd(DO3A-Lys), a macrocyclic gadolinium based MRI contrast agent functionalized with a lysine derivative, was studied in Wistar rats. Kinetic data was fitted using a two compartment model and revealed Gd(DO3A-Lys) to have a distribution half-life, t1/2(alpha), of 1.3 min, an elimination half-life, t1/2(beta), of 24.9 min and a large volume of distribution, VD, of 0.49 L/kg indicative of the agent being able to rapidly distribute into tissues and organs. Contrast enhanced magnetic resonance angiography (CEMRA) in an orthotopic U87MG glioma mouse model demonstrated considerable enhancement of both the tumor and surrounding vasculature after intravenous administration of Gd(DO3A-Lys). Applying dynamic contrast enhanced magnetic resonance imaging (DCEMRI) in the glioma of different sizes further showed distinct uptake characteristics and patterns of enhancement, which suggests the potential for differentiating changes at different stages of tumor growth. Our results indicate that Gd(DO3A-Lys) could be a promising candidate for glioma MR imaging.